Hubungan Body Comparison Dengan Body Dissastifaction Pada Remaja Putri Pengguna Instagram di Pekanbaru - Khairunnisa’ Syarif; Nor Kholifah; Renni Eviviola; Wita Indah Purnama (CV. Era Digital Nusantara, 2026)
The massive use of Instagram among adolescent girls often creates unrealistic beauty standards and triggers destructive physical appearance comparison behaviors. This study aims to determine the relationship between body comparison and body dissatisfaction among female adolescent Instagram users in Pekanbaru. A quantitative correlational research design was employed, involving 216 adolescent girls aged 10 to 20 years selected through purposive sampling. Data were collected using a body comparison scale and a body dissatisfaction scale. Hypothesis testing was conducted using the Pearson Product Moment correlation analysis. The results indicated a significant positive relationship between body comparison and body dissatisfaction (r = 0.246; p < 0.001). The higher the tendency of adolescent girls to engage in physical comparison, the higher their level of body dissatisfaction, with the correlation strength falling into the weak but definite category. The implication suggests the importance of strengthening media literacy and support so that adolescents can critically filter visual content to develop healthier body acceptance.